1974
DOI: 10.1136/gut.15.2.139
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vagotomy and drainage on the small bowel flora

Abstract: SUMMARY The incidence of small intestinal colonization in unoperated duodenal ulcer patients was low and similar to that in the normal population. The majority of patients seven to 10 days following truncal vagotomy and drainage were colonized whereas none of a control group of patients following simple closure of a perforated duodenal ulcer was colonized. In patients with pyloroplasty, this high incidence fell to control levels on average 18 months postoperatively, but in patients with a gastrojejunostomy, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…After proximal gastric vagotomy, however, resulting in a similar elevation of gastric pH, no change of jejunal microflora was found [59]. The same pattern is seen in clinical studies [16,58,60]. Changes of the anatomy and the parasympathetic innervation of the antroduodenal region after surgery may interfere with motility and clearance, and thus predispose to colonization with Gram-negative bacilli in the small bowel.…”
Section: Surgerymentioning
confidence: 52%
“…After proximal gastric vagotomy, however, resulting in a similar elevation of gastric pH, no change of jejunal microflora was found [59]. The same pattern is seen in clinical studies [16,58,60]. Changes of the anatomy and the parasympathetic innervation of the antroduodenal region after surgery may interfere with motility and clearance, and thus predispose to colonization with Gram-negative bacilli in the small bowel.…”
Section: Surgerymentioning
confidence: 52%
“…Such predisposing factors include diabetes, scleroderma, intestinal pseudo-obstruction, prior surgery (eg, terminal ileal resection), diverticulosis or strictures of the small bowel. 205 Gastric surgery, in particular that involving a blind loop, is associated with a high prevalence of SBBO: up to 50% of patients with gastrojejunostomy and vagotomy compared with 5% of those with vagotomy and pyloroplasty, 206 although the clinical significance of this finding is unclear. 207 Authors have also reported a high prevalence of SBBO in situations associated with achlorhydria such as old age or medical therapy with proton pump inhibitors.…”
Section: Tests For Malabsorptionmentioning
confidence: 99%
“…Vagotomy and hemigastrectomy (7,8), scleroderma (9), diabetic autonomic neuropathy (10), and idiopathic intestinal pseudo-obstruction (11) are diseases characterized by impaired motor function of the intestine and are associated with abnormal proliferation of bacteria within the lumen of the small intestine. A specific mechanism…”
Section: Introductionmentioning
confidence: 99%